(untitled) (Journal of Dhaka Medical College, 2020)
Diabetic nephropathy has some distinct stages and each of the stages are individually defined according to different amount of albumin excreted through urine. Serum creatinine is a very common tool of renal assessment in diabetic nephropathy. This study aims at observation of existing correlation between serum creatinine and urine albumin in diabetic nephropathy patients. This cross sectional observational study has been conducted on 50 diabetic patients admitted to medicine department of Dhaka Medical College Hospital. Patients were included in this study after fulfilling inclusion and exclusion criteria in a period January 2018 to June 2018. After selection, data were collected by structured questionnaire. Then 24 hour urinary total protein, urine for microalbumin, complete blood count, fasting blood sugar, two hours postprandial blood sugar, HbA1C, serum creatinine report were collected and analyzed it with the help of SPSS 16.0 MS excel. Among total 50 patients, 34 patients were diagnosed on the basis of microalbuminuria and the rest were found to have raised urinary total protein. The male patients were 54 percent of the total population. Most of the patients were in between the age of 57 to 67 years. The r value is insignificant in two graphs where serum creatinine was compared with urine microalbumin and serum creatinine respectively, which suggests absence of linear or any other correlation between these two components. The estimated Glomerular Filtration Rate (eGFR) was calculated by MDRD equation individually. Staging was done on the base of eGFR. Only 41.37% of the patients with microalbuminuria, showed eGFR consistent with its staging while only 31.5% of the patients with proteinuria showed respective expected eGFR. And the difference between the mean serum creatinine in two groups was insignificant. This study has shown that, the serum creatinine has no linear correlation with urinary albumin in diabetic nephropathy patients. So, commonly used serum creatinine based formula to calculate the estimated GFR cannot reflect the amount of urinary protein excretion all the time. So it can misinterpret the staging of the disease which can delay the appropriate treatment of the patient. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 141-147